Fitness Costs Associated to an Ile2041Asn Mutation in the Geophyte Sorghum halepense Resistant to ACCase-Inhibiting Herbicides - Panozzo, Silvia; Sattin, Maurizio (Frontiers in Agronomy, 2021)
Sorghum halepense (L.) Pers. is a troublesome weed of maize which reproduces through seeds and rhizomes. Resistance to ACCase-inhibiting herbicides due to a target-site mutation Ile-Asn in position 2041 of the ACCase gene was confirmed in several populations in Italy. The presence of fitness costs related to the allelic variant Ile2041Asn has never been investigated in ACCase-resistant S. halepense. Three growth analyses pot experiments were performed starting from rhizome buds (Exp1 and Exp3) or seed (Exp2). Plant development was monitored throughout the life cycle through destructive samplings. The mutation responsible for resistance to ACCase inhibitors was detected in all plants included in the experiments using a Cleaved Amplified Polymorphic Sequence method. Classical growth analysis was performed for the multiple sampling experiments (Exp1 and Exp2) and allometric relationships were calculated for the different dry weight plant parts in all experiments. Allometric relationships showed that susceptible (S) and ACCase resistant (R) biotypes allocated biomass differently in the reproductive structures: S populations allocated on average 30% more biomass in the panicles, whereas R populations allocated 12% more biomass to rhizomes than S populations. This was more evident when the experiments started from rhizomes buds. Reproductive allocation and reproductive effort were higher in S biotypes and R biotypes, respectively. The higher production of rhizomes and the lower production of seeds of the R biotype can significantly impact the evolution of herbicide resistance under continuous application of herbicides with the same mode of action. A medium-long term resistance management strategy which implements appropriate soil tillage and crop rotation taking into account the different reproductive attitude of biotypes S and R should be devised.